A Wideband Wide-Scan and Low-Profile Array Based on Enhanced Gain and High-Power Elements - Hongyin Zhang; Zhen Wang (IEEE Access, 2024)
A wideband wide-scan array based on dual-polarized elements is presented in this paper. The proposed element consists of two flared metallic wings and two shorting posts over a ground plane which is excited by a RF connector vertically. Without complex feeding network, the antenna element features wideband, low-profile, and high power handling capability. Besides, elements do not require electrical connection and can be arranged with gaps between neighbors, allowing for modular construction. The dual-polarized array in a square lattice can achieve wideband wide-scan performance. To verify the design, an $11× 11$ prototype has been fabricated and measured. The measurements of this prototype are presented and are in good agreement with the simulations. The results reveal that the array element can achieve a relative bandwidth of 100% for VSWR $\le 3$ at scans out to $θ \,\, = \,\, 45^{° }$ and an enhanced gain of 1 dB in lower frequency band. The array can obtain better than 20 dB polarization purity at 4 GHz and scan loss of lower than 3 dB over the band, respectively.